2013
DOI: 10.1186/2193-1801-2-178
|View full text |Cite
|
Sign up to set email alerts
|

Sedation of children for auditory brainstem response using ketamine-midazolam-atropine combination – a retrospective analysis

Abstract: Authors investigated sedation quality in children for auditory brainstem response testing. Two-hundred and seventy-six sedation procedures were retrospectively analyzed using recorded data focusing on efficacy of sedation and complications. Intramuscular ketamine-midazolam-atropine combination was administered on sedation preceded by narcotic suppository as pre-medication. On using the combination vital parameters remained within normal range, the complication rate was minimal. Pulse rate, arterial blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…23,27,28 It also enhances the benefit of the prophylactic coadministration of atropine (anticholinergic) as an adjunct in sedation with ketamine. it is in accordance with the findings of other studies which reported that it reduces the hypersalivation, excessive secretions of the respiratory tract, and nausea and vomiting, 29,30 which are the most common complications with ketamine. 5,31…”
Section: Discussionsupporting
confidence: 93%
“…23,27,28 It also enhances the benefit of the prophylactic coadministration of atropine (anticholinergic) as an adjunct in sedation with ketamine. it is in accordance with the findings of other studies which reported that it reduces the hypersalivation, excessive secretions of the respiratory tract, and nausea and vomiting, 29,30 which are the most common complications with ketamine. 5,31…”
Section: Discussionsupporting
confidence: 93%
“…Depending on the type and purpose of analysis, a non-cooperating patient may be treated with a pharmacological therapy based on sedatives, anesthetics, or a combination of the two [12] . The sedative agent generally used in the ABR survey is chloral hydrate, probably because it was the first molecule to be used [13] .…”
Section: Objectivementioning
confidence: 99%
“…26 It also confirms the benefit of the prophylactic coad ministration of atropine (an anticholinergic) as an adjunct to intravenous ketamine sedation in children. This is con sistent with many studies, which have reported that atro pine counters the effects of some sedatives, like ketamine, and reduces hypersalivation, excessive secretion from the respiratory tract, nausea, and vomiting, [27][28][29] which are the most common complications related to the use of keta mine. 6,7,30…”
Section: Orcid Idsmentioning
confidence: 59%